Sulfur-doped cyanobacterial biochar-supported Co-Fe spinel oxide with enriched oxygen vacancies: overcoming redox and electron transfer limitations in Fenton-like sulfadiazine removal - Chen He; Yaling Dai; Jinwei Wang; Zhiguo Lin; Linxin Zhao; Fengzhi Jiang; Xia Luo; Siping Ji; Xiangjun Yang (Bioresource Technology, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Covalent organic framework-mediated Nafion superhydrophobic coating for stabilizing the anode of aqueous zinc-ion batteries - Ling Zhong; Yimeng Yan; Zhixuan Ye; Xinxiang Zhang; Wenbin Yang; Jiaxian Zheng; Xiangfeng Lin; Linxin Zhang; Ge Zhou; Huiping Lin; Zhanhui Yuan (Chemical Engineering Journal, 2026)

Novel Perspectives Focused on the Relationship Between Herpesvirus Encephalitis and Anti-GFAP-Antibody-Positive Astrocytopathy - Yuqiao Liao; Linxin Wen; Ruoyi Zheng; Yinan Shen; Teng-Ai Ha; Mingkai Lin; Ruogu Cheng; Ye Gao; Pei Shang (Molecular Neurobiology, 2025)

Analysis of pathogenicity factors in the highly virulent Aeromonas hydrophila strain LP-2 - Lingli Lian; Lina Sun; Xinrui Zhao; Linxin Chen; Binghui Zhang; Yanling Liu; Xiangmin Lin (Aquaculture, 2025)

Morroniside improves AngII-induced cardiac fibroblast proliferation, migration, and extracellular matrix deposition by blocking p38/JNK signaling pathway through the downregulation of KLF5 - Haotian Zheng; Linxin Yang; Huashang Huang; Yazhou Lin; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Myocardial fibrosis (MF), which is an inevitable pathological manifestation of many cardiovascular diseases in the terminal stage, often contributes to severe cardiac dysfunction and sudden death. Morroniside (MOR) is the main active component of Cornus officinalis with a variety of biological activities. This study was designed to explore the efficacy of MOR in MF and to investigate its pharmacological mechanism. The viability of MOR-treated human cardiac fibroblast (HCF) cells with or without Angiotensin II (AngII) induction was assessed with Cell Counting Kit-8 (CCK-8). The migration of AngII-induced HCF cells was appraised with a transwell assay. Gelatin zymography analysis was adopted to evaluate the activities of MMP2 and MMP9, while immunofluorescence assay was applied for the estimation of Collagen I and Collagen III. By means of western blot, the expressions of migration-, fibrosis-, and p38/c-Jun N-terminal kinase (JNK) signal pathway-related proteins were resolved. The transfection efficacy of oe-Kruppel-like factor 5 (KLF5) was examined with reverse transcription-quantitative PCR (RT-qPCR) and western blot. In this study, it was found that MOR treatment inhibited AngII-induced hyperproliferation, migration, and fibrosis of HCF cells, accompanied with decreased activities of matrix metalloproteinase 2 (MMP2), matrix metalloproteinase 9 (MMP9), connective tissue growth factor (CTGF), Fibronectin, and α-SMA, which were all reversed by KLF5 overexpression. Collectively, MOR exerted protective effects on MF by blocking p38/JNK signal pathway through the downregulation of KLF5.

Formation mechanism and quantitative risk analysis of the landslide-induced hazard chain by an integrated approach for emergency management: A case study in the Bailong River basin, China - Yan Chong; Guan Chen; Xingmin Meng; Shiqiang Bian; Fengchun Huang; Linxin Lin; Dongxia Yue; Yi Zhang; Fuyun Guo (CATENA, 2023)

Recent advances in natural polysaccharides-based controlled release nanosystems for anti-cancer phototherapy - Haiting Xu; Wenbiao Nie; Linxin Dai; Ruifeng Luo; Dasheng Lin; Minyue Zhang; Jinming Zhang; Fei Gao (Carbohydrate Polymers, 2023)

Post-failure evolution analysis of an irrigation-induced loess landslide using multiple remote sensing approaches integrated with time-lapse ERT imaging: lessons from Heifangtai, China - Shiqiang Bian; Guan Chen; Runqiang Zeng; Xingmin Meng; Jiacheng Jin; Linxin Lin; Yi Zhang; Wei Shi (Landslides, 2022)